Daily Demonstrators The Civil Rights Movement in Mennonite Homes and Sanctuaries - Shearer, Tobin Miller (Johns Hopkins University Press, 2010)
The Mennonites, with their long tradition of peaceful protest and commitment to equality, were castigated by the Reverend Martin Luther King Jr. for not showing up on the streets to support the civil rights movement. Daily Demonstrators shows how the civil rights movement played out in Mennonite homes and churches from the 1940s through the 1960s.In the first book to bring together Mennonite religious history and civil rights movement history, Tobin Miller Shearer discusses how the civil rights movement challenged Mennonites to explore whether they, within their own church, were truly as committed to racial tolerance and equality as they might like to believe. Shearer shows the surprising role of children in overcoming the racial stereotypes of white adults. Reflecting the transformation taking place in the nation as a whole, Mennonites had to go through their own civil rights struggle before they came to accept interracial marriages and integrated congregations.Based on oral history interviews, photographs, letters, minutes, diaries, and journals of white and African-American Mennonites, this fascinating book further illuminates the role of race in modern American religion.